Religious Orientation and Health among Active Older Adults in the United States - Hunter, Bradley D. (Journal of religion and health, 2013)
This study utilizes a combination of intrinsic and extrinsic Religious Orientation Scales to explore the connection between religion and health in a sample of physically active, older adults. The revised Religious Orientation Scale and the RAND Short Form 36 (SF-36) were adopted to relate religious orientation (intrinsic, extrinsic, pro-religious, and non-religious) and self-rated mental and physical health status. Individuals of pro-religious orientation reported significantly worse health for physical functioning, role limitations due to physical health, and energy or fatigue when compared with those of all other religious orientations; however, no dose-response relationships were found between religious orientation and self-rated health. The results of this study indicate that deleterious health effects may accompany pro-religious orientation. Caution is provided for directors of religious programs for older adults.